If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2(x + -4) = 2x + -5 Reorder the terms: 3 + -2(-4 + x) = 2x + -5 3 + (-4 * -2 + x * -2) = 2x + -5 3 + (8 + -2x) = 2x + -5 Combine like terms: 3 + 8 = 11 11 + -2x = 2x + -5 Reorder the terms: 11 + -2x = -5 + 2x Solving 11 + -2x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 11 + -2x + -2x = -5 + 2x + -2x Combine like terms: -2x + -2x = -4x 11 + -4x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 11 + -4x = -5 + 0 11 + -4x = -5 Add '-11' to each side of the equation. 11 + -11 + -4x = -5 + -11 Combine like terms: 11 + -11 = 0 0 + -4x = -5 + -11 -4x = -5 + -11 Combine like terms: -5 + -11 = -16 -4x = -16 Divide each side by '-4'. x = 4 Simplifying x = 4
| 3(4x+1)=3+12x-2 | | (X+10)+(4x-20)=90 | | 7R*2+8R+8R= | | 3x(.29)=3 | | 1y+-4x= | | 8v-18=26+3v | | 18+4(-4)= | | 50-40x=200 | | 3t-t=20 | | X^5-2x^4+x^3-x^2+2x-1=0 | | 50+40x=200 | | 5a-2b=8displayngb | | 7+3k-4k=-5-3k | | -5g+1=7+2a | | 2n^3-24n^2-23048=0 | | 2y-4=10x | | 7T+8(7T+2)= | | 4(k+5)=2(9k-2) | | 24xy+6y=0 | | 9n-4n=4n+2n+7 | | 2(8n+6)=-3+n | | 5a-2b=8 | | 3c+2(4)=2 | | 21(7-y)+4=-4 | | 2(x-3)+2X=-14 | | 7-3(5-3v)-8=67 | | 6c=c | | x-6-26=7(x-26) | | Y+7-2=-5 | | x-6+26=7(x+26) | | 8(3B+5)+2= | | X^4-10*X^2-3*X+25=0 |